A quantum chemical cluster approach to study adsorption of some nitro compounds on the {100} α-quartz surface - Tsendra, O.; Gorb, L.; Lobanov, V.; Leszczynski, J. (2012)
This quantum chemical research, carried out using the density functional theory M06-2x DFT method with the 6‑31G(d,p) basis set and the three-layer ONIOM method (Gaussian09 program package), shows that alpha-quartz can moderately adsorb some nitrogen compounds, specifically, 2,4,6-trinitrotoluene (TNT),2,4-dinitrotoluene (DNT), 2,4-dinitroanisole (DNAn), and 3-nitro-1,2,4-triazole-5-one (NTO). The adsorption mechanism for all four considered nitro compounds was found to be similar. The main kind of surface binding is physical adsorption which occurs mainly due to hydrogen bonding, stacking interactions provided additional stabilization. From the Atoms-In-Molecules analysis of the studied systems it can be concluded that the adsorption energy is proportional to the number of intermolecular interactions between the target molecule and the surface. The energetically most favored position of the adsorbates over the mineral surface was found to be the parallel one. Квантовохимическое исследование с использованием теории функционала плотности методом M06-2x/6‑31G(d,p) и методом ONIOM-3 (программа Gaussian09) показало, что α-кварц способен адсорбировать 2,4,6-тринитротолуол, 2,4-динитротолуол, 2,4‑динитро-анизол и 3-нитро-1,2,4-триазол-5. Механизм адсорбции всех четырёх исследованных нитросоединений подобный – главная роль в связывании адсорбата с поверхностью принадлежит водородным связям, а стекинг-взаимодействия способствуют дополнительной стабилизации адсорбционных комплексов. Анализ изученных систем с помощью подхода «Атомы в молекулах» показал, что рассчитанная энергия адсорбции пропорциональна количеству связей между молекулами адсорбата и поверхностью. Установлено, что параллельное расположение молекулы нитросоединения по отношению к поверхности кварца является энергетически наиболее выгодным.